2006
DOI: 10.1007/11672142_35
|View full text |Cite
|
Sign up to set email alerts
|

Regular Expressions and NFAs Without ε-Transitions

Abstract: Abstract. We consider the problem of converting regular expressions into ε-free NFAs with as few transitions as possible. If the regular expression has length n and is defined over an alphabet of size k, then the previously best construction uses O(n·min{k, log 2 n}·log 2 n) transitions. We show that O(n · log 2 2k · log 2 n) transitions suffice. For small alphabets, for instance if k = O(log 2 log 2 n), we further improve the upper bound to O(k 1+log * n · n). In particular, O(2 log * 2 n · n) transitions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 14 publications
0
16
0
4
Order By: Relevance
“…Note that if ∆ is considered to be fixed, the upper bound for the regular expression-to-NFA conversion can be improved [15,28]. Combining the results of Lemmas 5.1 and 5.2 with any graph reachability algorithm we have: Theorem 5.1.…”
Section: Proof First Assume That L(a)mentioning
confidence: 82%
“…Note that if ∆ is considered to be fixed, the upper bound for the regular expression-to-NFA conversion can be improved [15,28]. Combining the results of Lemmas 5.1 and 5.2 with any graph reachability algorithm we have: Theorem 5.1.…”
Section: Proof First Assume That L(a)mentioning
confidence: 82%
“…Our algorithm does not assume a unit cost RAM model nor any restriction on the ratio between the size of the automaton t and the length of the sequences n. We further note that, in the case where the input is given in the form of a regular expression rather than an automaton, the complexity analysis of the algorithm can be expressed in terms of the length of the input regular expression. This is achieved based on recent algorithms which take as input a regular expression of length r and convert it into an e-free NFA with O(r) states and O(r log 2 r) transitions (Hromkoviěc et al, 2001;Schnitger, 2006;Geffert, 2003). This yields an O(n 2 r 2 log 2 r) time and O(n 2 r 2 ) space complexities for the algorithm of Chung et al We note that this was not observed by Arslan and Egecioglu (2005) and Chung et al (2007b).…”
Section: Resultsmentioning
confidence: 99%
“…A third possibility is to obtain a (ǫ-free) NFA through the reverse regular expression, which can be done in polynomial time [24]. For example, the forward regular expression corresponds to c*(w, b)*s*(w, b)* and the reverse regular expression corresponds to (w, b)*s*(w, b)*c*.…”
Section: Modeling Backward Path Viabilitymentioning
confidence: 99%